Foreword: International Dispute Resolution - Demystifying the New Frontier - Butler, Petra (Victoria University of Wellington Law Review, 2012)
As a trading nation and one that has always looked to the wider world, New Zealand's international engagement is key to the country's wellbeing and prosperity. Despite this, it seems that there is a lack of awareness and understanding of issues with regards to international dispute resolution in New Zealand. This article serves as a foreword for this issue of the Victoria University of Wellington Law Review which introduces the inaugural New Zealand Law Foundation International Dispute Resolution lecture given by Lucy Reed of Freshfields Bruckhaus Deringer, as well as the following seminar on the same issues.